2022
DOI: 10.1002/jcla.24526
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of neutrophil carcinoembryonic antigen‐related cell adhesion molecule 1 associated with multiple inflammatory mediators was related to different clinical stages in ischemic stroke patients

Abstract: Background: We aimed to analyze the level of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) in neutrophils of ischemic stroke (IS) patients at different stages, together with its roles in neutrophils.Patients and methods: Sixty-seven patients were classified into acute phase group (n = 19), subacute phase group (n = 28), and stable phase group (n = 20), and 20 healthy individuals who had received physical examination at the same time period as healthy control. We then analyzed the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the presence of LDNs in PBMCs may be associated with emergency hematopoiesis/granulopoiesis in these patients, 48 which is in agreement with the increase in the abundance of multiple inflammatory signals, such as IL-6, IL-8, IL-10, and G-CSF, which prolong the lifespan of neutrophils and infiltration 15 , 47 , 49 as well as high levels of neutrophil proliferation and degranulation marks 50 , 51 and leukocytes rolling mediators over vascular surfaces. 52 Additionally, the results of plasma biomarkers, particularly at D0 and D7, align with the state of inflammation and alterations of metabolic pathways observed in the proteome of PBMCs from these patients.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the presence of LDNs in PBMCs may be associated with emergency hematopoiesis/granulopoiesis in these patients, 48 which is in agreement with the increase in the abundance of multiple inflammatory signals, such as IL-6, IL-8, IL-10, and G-CSF, which prolong the lifespan of neutrophils and infiltration 15 , 47 , 49 as well as high levels of neutrophil proliferation and degranulation marks 50 , 51 and leukocytes rolling mediators over vascular surfaces. 52 Additionally, the results of plasma biomarkers, particularly at D0 and D7, align with the state of inflammation and alterations of metabolic pathways observed in the proteome of PBMCs from these patients.…”
Section: Discussionmentioning
confidence: 55%
“…When stroke occurs, reactive astrocytes, activated microglia, neurons, choroid plexus and endothelial cells synthesize and secrete LCN2 in response to inflammation or damage to the brain [ 34 ]. It is reported that elevated levels of LCN2 in human plasma 1–3 days after ischaemic stroke [ 35 , 36 ], and plasma LCN2 still has a high expression level in the subacute phase [ 37 ]. Significantly elevated LCN2 in cerebrospinal fluid (CSF) or peripheral blood is associated with poor functional prognosis after stroke [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant basic studies have shown that after ischemic stroke, elevated LCN2 activates various inflammatory pathways in glial cells, leading to glial cell proliferation, cytokine production and enhanced inflammatory response, so that neuroinflammation persists [ 34 ]. The abnormal increase of LCN2 not only directly destroys the BBB, but also forms a complex with matrix metallopeptidase-9 (MMP-9), which prolongs the activity of MMP-9 and participates in the destruction of the BBB [ 37 ]. Moreover, peripheral neurotoxic substances that pass through the damaged BBB also exacerbate neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The first cells to be activated following Ischemic brain damage are those of microglia. Subsequently, the monocytes/macrophages and the neutrophils also reach the ischemic area passing the blood–brain barrier (BBB) interacting with the adhesion molecules [ 26 , 27 ]. During reperfusion, glial cells and neurons secrete chemo-attractant protein-1 monocyte (MCP-1/CCL2), which causes the migration of neutrophils into the infarcted area [ 28 ].…”
Section: An Overview Of the Pathogenesis Of Cerebral Ischemiamentioning
confidence: 99%